Pengaruh Layanan Digital Syariah, Pendidikan, dan Sosialisasi Lingkungan terhadap Literasi Keuangan Syariah dengan Religiusitas Sebagai Moderasi - Repika; Ahmad Habibi; Gustika Nurmalia (Bulletin of Community Engagement, 2024)
Pre-research conducted by researchers on 30 respondents of Bank Syariah customers of Bandar Jaya Branch who have not met expectations. This is because the percentage of customers who have sharia financial products, understand about sharia financial products and institutions, and involve sharia principles in personal financial management is still quite low. This study uses a quantitative approach, data collection is carried out through a survey with a questionnaire. The population in this study were customers of Bank Syariah Bandar Jaya Branch. The sample of this study was 97 respondents, using SEM analysis tools using PLS and the results of data processing obtained using SmartPLS 4. The results of the study show that the variables of sharia digital services, education and environmental socialization have an effect on sharia financial literacy. Religiosity is able to moderate the influence of sharia digital services, education and environmental socialization have an effect on sharia financial literacy.